Measuring and Fitting the Relationship between Socioeconomic Development and Environmental Pollution: A Case of Beijing–Tianjin–Hebei Region, China. (2nd June 2019) - Meng, Ming; Pang, Tingting; Fan, Liguo
Abstract : The Beijing–Tianjin–Hebei (BTH) region is a top urban agglomeration of China but has the problem of severe environmental pollution. Most of the current researches on the sustainable development of this region only concentrate on the environmental pollution itself and ignore its relationship to the socioeconomic development. In this research, an entropy-based coupling model, a polynomial equation with partial least squares algorithm, and socioeconomic and environmental data in 2006–2015 were used to measure and fit the above relationship. Empirical analysis led to the following conclusions.( 1 ) Beijing, Tianjin, and Hebei presented similar socioeconomic development modes but different environmental pollution modes.( 2 ) The social economy of the BTH region has been developing at the expense of environmental pollution, but the environmental cost has been decreasing year by year.( 3 ) At present, the BTH region has huge potential to improve its environment.( 4 ) Increasing the investment in the treatment of industrial pollution in Tianjin and mitigating the soot (dust) emissions in Tianjin and Hebei are the major environmental policy directions.( 5 ) Controlling the development of smelting and pressing of ferrous metals and other building material sectors in Hebei is the major economic policy direction.